A Person-Centered Examination of Motivational Profiles and Employment Preferences Across Age Groups - Wang, Daisy; Wang, Zheni (Academy of Management Proceedings, 2026)
This cross-sectional study examines how age-group differences in work motivation and basic psychological needs relate to preferences between self- and wage-employment. Drawing on Self-Determination and Lifespan Development Theories, age groups are conceptualized as life-stage categories rather than birth cohorts, and motivational profiles are compared in the post-COVID US labor market. Online survey data were collected from 1,484 adult Americans across five age groups, from Gen Z to Traditionalist. Multi-group CFA for measurement invariance, ANOVA, latent mean comparisons, and latent profile analysis with distal outcome comparisons were performed. Results indicated significant, albeit small, age-group differences in employment preferences and motivational constructs. Gen Z-young adults reported relatively stronger preference for self-employment than older age-groups, whereas Gen Y (Millennials), early to mid-career, exhibited the highest autonomous motivation, the lowest amotivation, and greater satisfaction of autonomy and competence needs at work. Five distinct motivational profiles were identified from latent profile analyses; low-intensity and controlled–amotivated profiles were most strongly associated with a preference for self-employment, whereas a high-involvement yet conflicted profile showed the strongest preference for wage-employment. Younger participants, particularly Gen Z and Gen Y, were more likely to fall into globally elevated and psychologically complex profiles. Overall, the findings suggest that age-linked life stages are associated with nuanced motivational configurations that only modestly translate into employment preferences, highlighting the value of developmentally sensitive, person-centered approaches to understanding contemporary work, employment preferences, and entrepreneurial orientations.
Keywords: AOM Annual Meeting Proceedings 2026; AOM Philadelphia 2026; Human Resources; Paper - Abstract Only; dept.mgt

The Conditional Value of Consumer Satisfaction: Innovation Choice Under Economic Recession - Yoo, Jae Kyun; Lee, Minjae (Academy of Management Proceedings, 2026)
Economic recessions reshape consumer expectations and amplify scrutiny, altering how firms’ capabilities translate into performance. This study examines how recession-driven shifts in consumer expectations intensify the vulnerability of firms with high preexisting consumer satisfaction and how their innovation choices shape the extent to which this capability becomes a liability. We argue that recessions heighten negative reactions to perceived performance deviations, making high pre-recession satisfaction—typically a strategic strength—especially vulnerable. Using data from the U.S. automobile industry spanning the 2008 financial crisis, we find that consumer satisfaction declines significantly during recession and that firms with higher preexisting satisfaction experience disproportionately larger losses. We further demonstrate that innovation strategy plays a decisive moderating role: incremental product redesigns, which preserve familiarity and signal stability, mitigate the recession penalty for high-satisfaction firms, whereas new product introductions do not offer comparable protection. The study provides a theoretical account of how economic downturns can invert the value of demand-side capabilities and identifies conditions under which incremental innovation outperforms more transformative approaches. Managerially, the findings offer guidance on how firms can align innovation portfolios with shifting consumer psychology to protect reputational assets and sustain performance during an economic disruption.
Keywords: AOM Annual Meeting Proceedings 2026; AOM Philadelphia 2026; Paper - Abstract Only; Technology and Innovation Management; dept.mgt

The future is here! Recognizing the need to revitalize and transform business education via digital integration - Philip, Jestine; Schmidt, Gordon B.; Simha, Aditya; Rosen, David (Business Horizons, 2026)
Business education is undergoing rapid transformations thanks to advancements in emerging technologies. Business school leaders are engaging in identifying approaches to revitalize business education, preparing students to succeed in a technologically advancing workplace. Primarily anchored in the concept of digital transformation, our article provides practical guidance to help business schools integrate artificial intelligence (AI) into their curricula and infrastructure, benefiting students, faculty, administration, and leadership. We offer a roadmap that lays out current industry trends and articulates pertinent action items, related cost efforts, and associated benefits for business education. This article positions business schools to instill a human-AI augmentation mindset in students, faculty, staff, and leadership that prepares them to work with ever-changing technologies. Regularly revising business course curricula to stay aligned with evolving industry needs is key to providing topical content and meaningful skill development opportunities for students. We argue that these efforts directly enhance student employability and learning, better preparing students to succeed in the increasingly technology-enabled workplace. © 2026 Kelley School of Business, Indiana University. Published by Elsevier Inc. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Artificial intelligence (AI); Business schools; Digital transformation; Generative AI (GenAI); Human-AI augmentation mindset; dept.mgt

From fragmentation to integration: finding the psychological and instrumental common ground for algorithmic management and marketing - Wang, Zheni; Wang, Emma; Zhu, Guorong (SSRN Electronic Journal, 2026)
Keywords: Common ground; Corporate governance; Fragmentation (computing); Service (business); Spillover effect; Stakeholder; Stakeholder analysis; Stakeholder theory; dept.mgt; dept.mrk

Vacillation and performance: how alignment with environmental changes drives effective vacillation - Lee, MinJae (Academy of Management Proceedings, 2025)
Keywords: Empirical research; Environmental effect; Mechanism (biology); Period (music); dept.mgt

Developing entrepreneurship competence in STEM graduate students through a fellowship model - Wang, Zheni; Daneshmandi, Leila; Christodoulidou, Andri (Academy of Management Proceedings, 2025)
Keywords: Cognition; Competence (human resources); Entrepreneurship; Entrepreneurship education; Graduate students; Higher education; Mindset; Qualitative research; Value (mathematics); dept.mgt

Building positive experiences for sustainable development - Wang, Zheni; Zhu, Guorong; Zhang, Mengyi; Wang, Emma; Lv, Shuangning; Zheng, Jiawei; Shen, Yan; Steckler, Erica (Academy of Management Proceedings, 2025)
Keywords: Creativity; Face (sociological concept); Grounded theory; Stakeholder; Stakeholder engagement; Sustainability; Sustainable development; Work (physics); dept.mgt; dept.mrk

Museum experiences as innovative pedagogy in contemplative management education for sustainability - Yang, Charlie; Ivanova, Ekaterina; Ivanova, María (Academy of Management Proceedings, 2025)
Keywords: Contemplation; Curriculum; Environmental education; Experiential learning; Mindset; Reflective practice; Sustainability; Sustainable business; Visual arts education; dept.mgt

The relationship between quality management and innovativeness: an empirical study - Triana-Garcia, Randy; Muthuraj, Birasnav; Rincón-Guio, Cristian (6th South American Conference on Industrial Engineering and Operations Management, 2025)
This study aims to explore the relationship between four key elements of quality management: teamwork, feedback, motivational barriers, and need analysis, and their contribution to improve innovativeness in the Colombian educational context. Drawing on the concepts of control and learning in the quality management theory and using publicly available responses collected from the Colombian teachers who participated in the TALIS 2018 survey, this research study examines how teachers perceive these elements within their institutions and their potential impact on fostering innovativeness among teachers. The study adopts an empirical approach to analyze these relationships, employing a descriptive and inferential statistical framework to uncover patterns and correlations. By focusing on the school practices in Colombia, the research seeks to provide insights into how quality management practices can drive innovation in educational settings. Findings identify specific patterns in the implementation of these practices and their relationship with innovativeness among teachers, offering actionable recommendations for improving teaching strategies in education to improve quality. This study contributes to the broader understanding of management’s role in teaching and learning, offering valuable implications for policymakers and practitioners in developing countries. The novelty of this work lies in its analyses of TALIS data to assess quality management practices and their direct influence on fostering innovation.
Keywords: Business; Computer science; Empirical research; Knowledge management; Mathematics; Process management; Quality (philosophy); Statistics; dept.mgt

Bridging indigenous art and sustainability: transformative museum learning in management education - Yang, Charlie (Humanistic Management Journal, 2025)
Keywords: Bridging (networking); Computer science; Ecology; Environmental ethics; Indigenous; Pedagogy; Philosophy; Sociology; Sustainability; Transformative learning; dept.mgt

How Do Firms Build Green Supply Chain Learning System? A Theoretical Framework and Directions - Birasnav, M.; Han, Seungmin; Arora, Ridhi; Sangar, Ruby (Corporate Social Responsibility and Environmental Management, 2026)
Keywords: Green innovation; Mechanism (biology); Perspective (graphical); Resource (disambiguation); Supply chain; Supply chain management; Workforce; corporate social responsibility; dept.mgt; environmental performance; exploitation; exploration; green supply chain; leadership; learning system

Framing the future: how museums shape sustainability mindsets in business education - Yang, Charlie; Ivanova, Ekaterina; Ivanova, Maria (The Power of Arts-Based Pedagogies: Transforming Mindsets to Shape Our Future, 2026)
Recent research proposes that arts-integrated teaching approaches in business education can nurture students' aesthetic sensitivity and emotional capacities, such as self-awareness and empathy. In this chapter, we examine the pedagogical possibility of art appreciation in art museums as a consciousness-raising practice, especially for the sake of cultivating business students' environmental awareness in two different contexts. We have analyzed American and Russian students' reflective essays based on their museum visits in order to explore how business students make sense of their aesthetic experiences and how art appreciation helps them to develop their sustainability mindset in a creative learning space. Through attentive viewing of the works of art, students have learned some key insights from their aesthetic appreciation at art museums. These insights not only facilitated honing their emotional skills, but also deepened their environmental awareness and heightened their sense of personal empowerment to act upon these newly acquired insights and values ensuing from art appreciation. After identifying six key themes extracted from both groups of students' essays based on their museum learning, we further discuss the pedagogical implications of contemplative art appreciation in museums as a means of contributing to more innovative and sustainable management education. © 2026 selection and editorial matter, Ekaterina Ivanova, Isabel Rimanoczy and Divya Singhal; individual chapters, the contributors.
Keywords: dept.mgt

Quality management and safety performance: the influence of ethical leaders among public sector employees - Birasnav, M.; Dahiya, Rinki; Dalpati, Avadhesh (The TQM Journal, 2026)
Keywords: Ethical leadership; Incentive; Job satisfaction; Motivation for QM implementation; Perceived safety performance; Public sector; Quality (philosophy); Structural equation modeling; Survey data collection; Test (biology); Work (physics); dept.mgt

Rethinking Motivation and Reward Management: What We Know and Do not Know - Wang, Zheni (Edward Elgar Publishing Ltd., 2025)
This innovative book examines the controversial relationship between motivation and rewards from multiple theoretical and practical perspectives. It analyzes cutting-edge research on work motivation and reward management's economic and psychological roots and identifies future directions for advancement in the field. © Zheni Wang 2025.
Keywords: Compensation And Benefits; Motivation At Work; Reward Management; Self-Regulations; Total Rewards; Work Engagement; dept.mgt

Understand the Changes in Motivation at Work: Empirical Studies Using Self-Determination Theory-Based Interventions - Wang, Zheni; Briand, Mélanie (Behavioral Sciences, 2025)
Managers often need to stay motivated and effectively motivate others. Therefore, they should rely on evidence-based interventions to effectively motivate and self-motivate. This research investigated how self-determination theory-based interventions affect employees' motivation dynamics and motivational consequences within short time frames (i.e., within an hour, within a few weeks or months) in two empirical studies. Study one focused on assessing the effectiveness of a one-day training workshop in helping to improve managers' work motivation, basic psychological needs satisfaction/frustration, subordinates' motivation, and perceptions of managers' needs-supportive/thwarting behaviors within a few weeks. Results support the effectiveness of the training, as managers were rated by their direct subordinates as having fewer needs-thwarting behaviors and reported self-improvement in needs satisfaction and frustration six weeks after completing the training program. Study two used the mean and covariance structure analysis and tested the impact of three types of basic psychological needs-supportive/thwarting and control conditions (3 × 2 × 1 factorial design) on participants' situational motivation, vitality, and general self-efficacy for playing online word games within 30 min. Multi-group confirmatory factor analysis (CFA) confirmed the scalar measurement invariance, then latent group mean comparison results show consistently lower controlled motivation across the experimental conditions. During a quick online working scenario, the theory-based momentary intervention effectively changed situational extrinsic self-regulation in participants. Supplementary structural equation modeling (SEM; cross-sectional) analyses using experience samples supported the indirect dual-path model from basic needs satisfaction to vitality and general efficacy via situational motivation. We discussed the theoretical implications of the temporal properties of work motivation, the practical implications for employee training, and the limitations.
Keywords: Applied psychology; Autonomy; Computer science; Confirmatory factor analysis; Psychological intervention; Psychology; Self-determination theory; Situational ethics; Social psychology; Structural equation modeling; Work (physics); Work motivation; dept.mgt; employee training and development; motivation change; self-determination theory; theory-based interventions

Gender congruence and entrepreneurial investments: the role of others’ reactions - Wieland, Alice (International Journal of Gender and Entrepreneurship, 2025)
The purpose of this research is to explore the decision processes that underlie the gender gap in entrepreneurial investments. The present research explores how gender congruence with a sex-typed business opportunity influences anticipated reactions from others who may provide or withhold support and resources, how these affect the assessed probability of venture success and the amount the entrepreneur is willing to invest (WTI) in the opportunity.,A theoretical model is presented and empirically tested via path analysis. A pilot and an experimental study model explore how gender congruence influences entrepreneurial investment decisions. The experimental study uses a repeated measures design examining the experimental effects two sex-typed business opportunities crossed with participant gender (gender congruence) on anticipated others’ reactions, assessed probability of venture success and investment amount (WTI).,Gender congruence of a business opportunity influences anticipated others’ reactions, whether they will be supportive or not, of pursuing the opportunity. This in turn influences the estimated probability of success of the venture and the amount the prospective entrepreneur is willing to invest in it. These socio-cognitive decision processes reinforce the gender gap in entrepreneurship since participants anticipate less access to others’ support for gender incongruent opportunities. Although the mediational model indicates most proposed relationships and paths are invariant across genders, the exception was that women did not report higher WTI for the gender congruent venture.,The research applies the latest thinking in social psychology on gender norm violations to entrepreneurship, measuring how anticipated reactions from others are a factor in predicting estimates of venture success probability and self-investments.
Keywords: dept.mgt; peer-reviewed

The Impact of Attentiveness Interventions on Survey Data - Fuller, Christie; Simmering, Marcia; Waterwall, Brian; Ragland, Elizabeth; Twitchell, Douglas; Wall, Alison (Educational and Psychological Measurement, 2025)
Social and behavioral science researchers who use survey data are vigilant about data quality, with an increasing emphasis on avoiding common method variance (CMV) and insufficient effort responding (IER). Each of these errors can inflate and deflate substantive relationships, and there are both a priori and post hoc means to address them. Yet, little research has investigated how both IER and CMV are affected with the use of these different procedural or statistical techniques used to address them. More specifically, if interventions to reduce IER are used, does this affect CMV in data? In an experiment conducted both in and out of the laboratory, we investigate the impact of attentiveness interventions, such as a Factual Manipulation Check (FMC) on both IER and CMV in same-source survey data. In addition to typical IER measures, we also track whether respondents play the instructional video and their mouse movement. The results show that while interventions have some impact on the level of participant attentiveness, these interventions do not appear to lead to differing levels of CMV.
Keywords: Affect (linguistics); Applied psychology; Communication; Mathematics; Medicine; Post hoc; Psychological intervention; Psychology; Quality (philosophy); Social psychology; Statistics; Survey data collection; Survey research; dept.mgt; peer-reviewed

Bridging employees’ perceptions of corporate social responsibility, sense-making for meaningfulness, and work engagement for successful self-regulation - Wang, Z.; Carroll, S.; Wang, E.H. (Behavioral Sciences, 2024)
In response to calls for research on the psychological mechanisms, such as perceptions and attitudes toward corporate citizenship, in promoting positive outcomes at work, this research presents a novel approach by empirically testing a calling conditioned path model from P perception of corporate CSR (P-CSR) to work engagement via meaningfulness under the theoretical framework of self-determination theory. Survey data collected from 224 corporate employees in the US were tested using the PROCESS plugin (version 4.3) in SPSS. The regression results supported the positive direct and indirect paths from employees’ P-CSR to meaningfulness and work engagement but not the conditioning effect of calling work orientation. This study’s unique findings, limitations, future research, and implications are discussed, expanding micro-CSR research and unboxing the management assumptions of employees as purposeful autonomous agents seeking consistent interpretations and authentic perceptions of organizational CSR activities during their sense-making processes. Non-confirming of the calling conditioning the path model shed light on it being a dynamic multi-dimensional and multi-level construct to be further researched. © 2024 by the authors.
Keywords: calling work orientation; dept.mgt; micro-CSR; peer-reviewed; work engagement

A metacognitive approach to understanding what marker variables measure - Leonard, Stephanie; Simmering, Marcia J.; Wall, Alison E. (Current Psychology, 2024)
Marker variables provide an efficacious means of post hoc detection of common method variance (CMV) in data. These variables are measured in the same way as substantive variables, but because they are conceptually unrelated to the variables of interest, they are believed to be a proxy for CMV. Although marker variables have demonstrated effectiveness, questions remain as to what they actually measure, and thus, why they work. This lack of knowledge prevents researchers from choosing appropriate marker variables to include in same source surveys. The purpose of this research is to determine how four different marker variables account for common rater effects which can cause CMV. A metacognitive approach is used to develop an empirical study using two samples, with a focus on the specific rater effects of mood state, transient mood, consistency motif, and illusory correlations. Findings indicate that these marker variables elicit similar respondent reactions and do not create a notable psychological separation between substantive variables. Additionally, there is evidence that respondents’ use of consistency motifs and illusory correlations influence substantive variable relations. Finally, using the confirmatory factor analysis marker technique, data from two samples indicate the presence of CMV, but not bias from CMV, indicating that the problem of artificially inflated results due to CMV may be overstated.
Keywords: Common method variance; Marker variables; Metacognition; Survey research; dept.mgt; peer-reviewed

The interplay of power, incentives, academic freedom, and gender equity - Wieland, Alice; Jansen, Amy (Journal of Academic Freedom, 2024)
Alice Wieland and Amy Jansen explore the intersection of how power, adverse incentives, and gender bias combine to perpetuate gender inequity in higher education.
Keywords: dept.lib; dept.mgt

Do schools have hindrance of quality to promote innovativeness? Examining the role of empowering leadership and stakeholder involvement - Birasnav, M.; Dahiya, Rinki; Bharti, Teena (International Journal of Quality & Reliability Management, 2024)
Purpose Schools provide high priorities to offer innovative curricular and cocurricular programs, and leaders make necessary efforts to promote enablers and overcome disablers for sustaining their innovativeness. With the background of quality management and stakeholder theories, the present study examines the interplay of hindrances to quality between empowering leadership, stakeholder involvement and organizational innovativeness. Design/methodology/approach Responses of 157 American school principals collected through the Teaching and Learning International Survey 2018 by the Organization for Economic Cooperation and Development were used and analyzed to test the proposed hypotheses. Findings Results show that empowering leadership behaviors of school principals support promoting organizational innovativeness, and involvement of stakeholders with the school activities also promotes organizational innovativeness. Interestingly, when American schools faced a high level of hindrance to providing quality education to their students, principals’ high level of empowering leadership behaviors promoted organizational innovativeness. Originality/value This is the first time in the literature that the interplay between empowering leadership, stakeholder involvement and hindrance of quality education has been examined to promote organizational innovativeness.
Keywords: Empowering leadership; Hindrance of quality education; Organizational innovativeness; Quality management; Stakeholder involvement; dept.mgt; peer-reviewed

Unboxing the temporal patterns of employee engagement: a daily and weekly analysis of needs satisfaction, work motivation and employee well-being - Wang, Z. (Evidence-based HRM, 2024)
Purpose: This research used a temporal approach to operationalize employee engagement, capturing subjective/objective time of the day and day of the week to analyze the dynamic patterns of employees’ daily/weekly well-being, basic needs satisfaction, and situational work motivation under the integrated framework of self-determination theory. Design/methodology/approach: Multi-level data was collected using the survey structure outlined under the day reconstruction methodology (DRM) with samples of Canadian part-time working undergraduate students and full-time US corporate employees (1980 work episodes reported by 321 participants). Findings: Multi-level confirmatory factorial analysis results supported the measurement invariance for within-person variables in all the working episodes across the US and Canada samples. Structural equation modeling path analysis results, using the within-person variables, captured the daily temporal patterns that employees’ well-being (vitality and positive affect), basic psychological needs (autonomy and relatedness), and situational autonomous motivation started at a high level and decreased with both subjective and objective time of the day. Negative affect showed asymmetric daily and weekly temporal patterns compared to positive affect. A few indirect paths were found, including one from the subjective time of the day to employee well-being (vitality and affect) via situational autonomous motivation and another one from the day of the week to vitality and positive affect via relatedness needs satisfaction and situational autonomous motivation. Research limitations/implications: The socio-cultural and business impacts of work scheduling practices and implications for theory-driven, evidence-based organizational development practices were discussed together with the research limitations. Practical implications: Results on how the variations in self-regulation during the performance of different work tasks in a single work event help practitioners to connect repeated situational motivational change patterns to effective supervision. HR business partner can also utilize such findings to shape evidence-based practice to improve employee engagement. Originality/value: This research is one of the few pioneer studies to look into how temporal factors, such as work scheduling, affect employees' well-being through the dynamic understanding of the mediated path model from time to employee well-being via psychological engagement conditions such as motivation and needs satisfaction. © 2024, Emerald Publishing Limited.
Keywords: Self-regulation; Temporal analysis; Work scheduling; dept.mgt; peer-reviewed

Perspectives on Product Stewardship - Cassel, Scott (Bernan Press, 2023)
Keywords: dept.mgt

Gendered cognitions: a socio-cognitive model of how gender affects entrepreneurial preferences - Wieland, Alice M.; Kemmelmeier, Markus; Gupta, Vishal K.; McKelvey, William (Understanding Women's Entrepreneurship in a Gendered Context, 2021)
Keywords: dept.mgt; peer-reviewed

Staying Alive: Leadership in COVID-19 World - Stewart, Carol (Journal of Leadership, Accountability & Ethics, 2021)
While this unprecedented time of COVID-19 has resulted in financial loss for many companies, it's also produced new leadership opportunities. Remote work, at-home schooling, and socially-distancing are a few examples of the new norm and new business possibilities. As crisis proverbially breeds innovation, new businesses have already sprung up around the world in support of growing demands. History shows this growth in entrepreneurial endeavors to be a trend during times of economic downturn. More than half of 2009 Fortune 500 list and just under half of 2008's Inc. list were created during a recession or bear market. Challenging economic times often seed the growth of entrepreneurial capitalism. One reason for this growth is that startup companies begun during times of high stress tend to be capable of operating in less favorable conditions. In times of economic upheaval, even mature businesses with longer history and deeper pockets require special leadership to 'pivot' their operational strategies to stay viable. This paper explores effective leadership theories to explain the success during uncertain times.
Keywords: BEAR markets; COVID-19; LEADERSHIP; NEW business enterprises; SITUATIONAL leadership theory; TELECOMMUTING; dept.mgt; entrepreneurship; leadership; pandemic; peer-reviewed; pivoting; situational leadership

Business succession planning: a vital component to the success and longevity of small businesses - Smith Jr, Robert A.; Badr, Kauther S. (International Academy of Business Disciplines 24th Annual Conference, 2023)
Keywords: dept.mgt

Improving school performance and student academic orientation: the role of safety-oriented knowledge management and diversity - Birasnav, M.; Gantasala, Prabhakar Venugopal; Gantasala, Swapna Bhargavi (VINE Journal of Information and Knowledge Management Systems, 2021)
Purpose The purpose of this study is to examine the influence of the implementation of safety-oriented knowledge management (KM) processes and student diversity acceptance in schools and the interaction effect of safety-oriented KM processes and student diversity acceptance over school performance and student academic orientation. Design/methodology/approach Responses of 977 American schools available in the database of the National Center for Education Statistics were analyzed using hierarchical regression analyses. Findings Results show that implementation of safety-oriented KM processes and diversity acceptance in schools have varying effects on school performance and student academic orientation. The impact of knowledge acquisition from parents on the academic achievement of students is positive and stronger in schools that are low in student diversity acceptance than schools that are high in student diversity acceptance. Originality/value This study adds value to the KM literature by exploring how KM processes are executed in American schools to improve their performance and students’ academic orientation and how diversity among students alters the strength of the relationships.
Keywords: Diversity acceptance; Knowledge management processes; School performance; School safety; Student academic orientation; dept.mgt; peer-reviewed

Routing vehicles through cross-docking facility for third party logistics service providers - Birasnav, M.; Kalaivanan, S.; Ramesh, A.; Tibrewala, Rajendra (International Journal of Operational Research, 2020)
This study focuses on a specialised vehicle routing problem (VRP) to transport matchboxes from manufacturing companies to retailers through a cross-dock (cross-docking facility) operated by a third party logistics service provider. Three processes (unloading, consolidating, and loading) are carried out at a cross-dock for completely avoiding or keeping inventory for a very short time. The specialised VRP, addressed in this paper, consists of multiple suppliers (each supplier can produce different brands of products for any number of customers) and multiple customers (each customer can receive orders from any number of suppliers). A mixed integer linear programming model has been developed to solve this kind of NP-hard problem. The objective of this model is to minimise total cost incurred in picking up and transporting the matchboxes from the manufacturers to cross-dock, consolidating matchboxes at cross-dock, and in transporting and delivering the matchboxes to the customers. This study also proposes an effective heuristic procedure to solve the same problem and compares the solution obtained using the heuristic procedure to the optimal solution obtained using the exact method. The findings show that the heuristic method, proposed by us, generates near optimum solutions using significantly less computational time than the exact method.
Keywords: NP-hard; consolidating; cross-docking; dept.mgt; heuristic; logistics service provider; multiple customers; multiple suppliers; peer-reviewed; vehicle routing

Performance evaluation of geospatially assisted reference evapotranspiration models - Pandi, Dinagarapandi; Saravanan, Kothadaramanan; Kuppusamy, Mohan; Birasnav, M. (Arabian Journal of Geosciences, 2022)
Mapping of spatiotemporal distribution of evapotranspiration becomes important for sustainable water management as water scarcity is nowadays a growing concern in almost all the continents. In general, researchers estimate evapotranspiration by multiplying the computed reference evapotranspiration (ETo) with the corresponding crop coefficient. Such estimation of ETo requires data related to spatiotemporal meteorological and vegetation field characteristics, and however, these data are rarely available in most developing countries such as India. Thus, researchers constantly develop various methods and evaluate the applicability of these methods to accurately capture spatiotemporal distribution. The purposes of this study are to (a) examine the applicability of Hargreaves and MODIS ETo method to map the spatiotemporal distribution over Thamirabarani basin located in Southern India and (b) evaluate the performances of Hargreaves and MODIS ETo methods and compare it to FAO 56 Penman–Monteith method. To achieve these purposes, ETo data of Hargreaves method and MODIS ETo method over Cheranmadevi meteorological observatory are extracted and performances of these methods are compared with FAO 56 Penman–Monteith method. Results show that a match exists among all the three ETo datasets, and no major deviations have been observed. However, this study suggests local calibration of Hargreaves and MODIS ETo method as considerable mismatch has been observed at ETo daily value. Overall, the conclusion of this study encourages the application of the Hargreaves method and MODIS ETo method in developing countries, where the data shortage condition prevails.
Keywords: Evapotranspiration; FAO 56 Penman–Monteith method; Hargreaves method; MODIS ETo; Thamirabarani basin; dept.mgt; peer-reviewed

Green supply chain management: A theoretical framework and research directions - Birasnav, M.; Chaudhary, Richa; Henry Dunne, James; Bienstock, Joshua; Seaman, Cristina (Computers & Industrial Engineering, 2022)
Practitioners and academicians dedicate significant attention to tackling initiatives and executing mechanisms to address society’s environmental concerns. Further, organizations and researchers recognize that there is a need to implement green supply chain management (GSCM) practices as a part of green strategy. To date, embedding a sustainability dimension into supply chain management remains a challenge for organizations given the lack of systematic knowledge of the key dimensions of GSCM practices, the factors that influence the implementation of GSCM practices, and the benefits that organizations gain through the implementation of such practices. To address this problem, this study reviews 151 research articles published between 1997 and 2021 in the GSCM literature, and offers a theoretical framework that synthesizes and integrates the knowledge acquired from the reviewed literature. This framework includes various dimensions of GSCM practices identified in the past research studies, the antecedents that influence implementation of GSCM practices, and the outcomes of implementation of such practices. Further, this study offers theoretical and practical perspectives to support future research utilizing a research model as a baseline to guide organizations in the understanding of the primary GSCM attributes, their predictors, and benefits.
Keywords: Antecedents; Green supply chain; Outcomes; Systematic literature review; dept.mgt; peer-reviewed

Ease of market entry of Indian startups: formal and informal institutional influences - Scillitoe, Joanne L.; Birasnav, Muthuraj (South Asian Journal of Business Studies, 2021)
Purpose The purpose of this study offers a theoretical model, hypotheses and empirical analyses of how formal and informal institutions influence the ease of market entry of startups in the context of India. Design/methodology/approach A theoretical model based upon institutional and market entry theories is presented with hypotheses. Structural equation modeling is used to test the hypotheses. Findings Results of the study suggest that college preparations and a culture of creativity and innovation are positively related to ease of market entry by Indian startups. A culture of personal success is negatively related to ease of market entry. Government assistance related to ease of market entry is not significant. Originality/value This paper offers a new perspective, linking formal and informal institutional influences to startup ease of market entry. In addition, informal institutions are viewed from the cultures of personal success and creativity/innovation within the entrepreneurial domain, which is also new to the literature. This paper offers specific insights in the context of India startups and offers some interesting findings that can contribution to the literature, policy and practice.
Keywords: Culture; Entrepreneurship; India; Institutions; Market entry; Startup; dept.mgt; peer-reviewed

Total quality leadership and organizational innovativeness: the role of social capital development in American schools - Birasnav, M.; Gantasala, Swapna Bhargavi; Gantasala, Venugopal Prabhakar; Singh, Abhishek (Benchmarking: An International Journal, 2022)
Purpose The purpose of this study is to explore the relationship between total quality leadership, social capital development and organizational innovativeness in the school environment. While there are research studies focused on the impact of leadership on implementing quality management practices, innovation and organizational performance, the mediating effect of social capital development has not been explored on the influence of the school leaders. Design/methodology/approach To achieve the purpose of this study, data collected from 158 principals, who participated in the Teaching and Learning International Survey 2018, were analyzed using structural equation modeling. Findings This study found that total quality learning-oriented school leaders are supportive of developing social capital in their schools, and such social capital development is very useful to improve organizational innovativeness. Interestingly, social capital development has been found to mediate the relationship between total quality learning-oriented school leadership and organizational innovativeness. Practical implications This study submits evidence for two major activities that school leaders perform: learning- and control-oriented activities, both being important for improving and measuring quality in the educational sector. This study clearly shows that control-oriented activities lean toward negatively on social capital while learning-oriented activities strongly and positively influence social capital development. From this study, practitioners can be aware and consciously promote social capital development in schools and that social capital development mediates the influence of total quality leadership and innovation in schools. Originality/value Schools can be visualized as guarded communities for creating a secure environment for students in support of learning. This research study shows that the combined cognitive capital, structural capital and relational capital mediate the impacts of total quality leadership on innovativeness in schools. Thus, school leaders should first establish a mechanism to develop social capital among their employees to bring up innovative initiatives.
Keywords: Organizational innovativeness; School leaders; Social capital; TALIS; Total quality leadership; dept.mgt; peer-reviewed

Cash Holdings and Firm Performance in the Restaurant Industry - Kim, Jung Hoon; Lim, Jaeseong; Ahn, Jin Sun; Kim, Youngbin (Journal of Applied Business and Economics, 2023)
This study explores the link between cash holdings and performance outcomes in public restaurant companies in the United States, leveraging the critical role played by the industry context. We hypothesize that cash holdings have positive associations with both short-term and long-term firm performance in the restaurant industry. Our empirical analyses, based on fixed-effect regression models that control for all time-invariant variables, reveal that holding cash can improve performance in the restaurant industry, in support of our hypotheses.
Number: 3
Keywords: dept.mgt; firm performance; peer-reviewed

Recruiting and Retaining the Genius Generation for Virtual Teams from a Generation Z Perspective - McGraw, Laquita; Stewart, Carol (International Journal of Business Research & Information Technology (IJBRIT), 2020)
The concept of a virtual team is expanding as its application is growing with multiple generations in the workforce. A virtual team is now a significant issue in the 21st century because there are currently five generations in the workforce. To lead a multigenerational virtual team, employers must understand a new generation that is entering the workplace. Although Generation Z will bring new characteristic to the workforce, leadership styles must transform to accommodate a newer generation's expectations. This study explores leadership styles to support virtual teams and a new generation. There exist only a few qualitative studies on virtual teams in today's domestic workforce. The researchers wish to gain knowledge of which leadership style works for a virtual team from the perspectives of Generation Z.
Keywords: GENERATION Z; GENIUS; Generation Y; Generation Z; LEADERSHIP; TEAMS; VIRTUAL communities; VIRTUAL work teams; Virtual team; dept.mgt; leadership; peer-reviewed

Leadership and Corporate Social Responsibility in Sports: If You’re Not First, You’re Last - Stewart, Carol; Marciniec, Sheryl; Joyner-McGraw, Laquita; Han, Seungmin (International Journal of Business and Public Adminstration, 2020)
Keywords: dept.mgt; peer-reviewed

Characteristics of Effective Trade Secrets and Confi dential Information Policies: Guidance from Labor Arbitration Cases - Ross, William H.; Franklin, Danny (Labor Law Journal, 2020)
In an effort to craft recommendations to managers regarding effective confidential information policies, the present paper reviewed 88 published grievance arbitration cases involving proprietary information, trade secrets, and confidential information. Most cases dealt with the application of managerial discipline for employee violations of company polices and collective-bargaining provisions. Themes that emerged included: the importance of a Management Rights clause (as well as specific Misconduct clauses and policies), clauses that address changing business conditions (such as subcontracting and new technology), employee insubordination, theft, falsification, conflict of interest, and the need for training. Additionally, arbitrators often considered specific laws that apply in health care, cable television, and telecommunications industries. Finally, several mitigating factors were noted such as: having permission from a supervisor to access confidential information, safety, and whistleblowing concerns. By attending to factors that influence arbitrator decision making, managers and their attorneys can use these identified factors to create better policies and negotiate robust collective bargaining provisions.
Num Pages: 43-57 Place: Riverwoods, United States Publisher: CCH Incorporated: Health & Human Resources
Keywords: Arbitration; Business And Economics–Labor And Industrial Relations; Collective bargaining; Competition; Competitive advantage; Conflicts of interest; Discipline; Employees; Espionage; Fair & Accurate Credit Transactions Act 2003-US; Information policies; Intellectual property; Labor law; Law; dept.mgt

Advice-Taking in Ethical Dilemmas - Franklin, Danny; Guerber, Amy J. (Editorial Policy, 2020)
Keywords: dept.mgt; peer-reviewed

The Reciprocal Relationship between Containers Overboard and Climate Change - Daniel, J.; Stapleton, K. A.; Stapleton, D.; Nandialath, A.; Franklin, D. (Journal of Transportation Law, Logistics, and Policy, 2021)
Not only does the flotsam and jetsam in the world’s oceans seem to be impacting the health of the world’s oceans and seas, but it appears that the warming climate and increasing CO2 emissions are impacting the global trade lanes evidenced by a greater-than-average number of lost maritime containers due to resultant rougher seas and stronger storms. We elucidate the evolution of containerized shipping and discuss the impact lost containers have on the seas and dangers to other ocean-going vessels. We also note the reciprocal effects between climate change and lost containers. The intent of our article is to shed light on these issues and we hope it sparks future research examining causal factors and their potential solutions.
Keywords: dept.mgt; peer-reviewed

Home Address Exemptions in State FOI Laws - Gil, Jodie; Smith, Robert A.; Badr, Kauther S. (The Journal of Civic Information, 2022)
Number: 4
Keywords: dept.mgt; peer-reviewed

Towards an integrated understanding of art, spirituality, and well-being - Yang, Charlie (Journal of Management, Spirituality & Religion, 2023)
Keywords: dept.mgt; peer-reviewed

The Escalating Competition Faced by Netflix - Jin, Sun Ahn; Jung, Hoon Kim; Youngbin, Kim; Jaeseong, Lim (Journal of Accounting-Business dan Management, 2023)
Num Pages: 1
Keywords: dept.mgt; peer-reviewed

The Effect of Market-Entry Timing on a Firm’s Speed and Cost of Entry - Lee, Minjae (American Journal of Management, 2023)
This paper examines the effect of market-entry timing on a firm’s speed and cost of entry in a setting where a firm needs to build a plant for market entry. Based on our developed analytical model, we provide seven scenarios of the market-entry timing effect on a firm’s entry speed and cost. We test hypotheses in the liquefied natural gas (LNG) industry. We use Wooldridge’s three-step instrumental variable (IV) approach to account for endogeneity bias. We find that a late entrant has (1) a shorter time-to-build and (2) a higher cost-to-build relative to an early entrant. Further, (3) the late entrant positively moderates the negative relationship of time-to-build and cost-to-build (i.e., the negative relationship of time-to build and cost-to-build becomes less negative for the late entrant). These empirical results are consistent with the prediction of when both revenue effect (i.e., revenue curve shift) and cost effect (i.e., cost curve leftward shift) exist.
Number: 3
Keywords: dept.mgt; peer-reviewed; time compression diseconomies

Developing the Construct of Speed Ceteris Paribus - Lee, Minjae (Academy of Management Proceedings, 2023)
Firm speed has long been a construct of interest among managers and researchers. Despite its importance, making a ceteris paribus comparison of speed can be challenging. In the current paper, we suggest an alternative to the conventional way of capturing the speed ceteris paribus. First, we illustrate the concept of faster speed in strategic management research. Second, we use numerical simulation data to illustrate the challenges of the conventional methodology, known as the nonlinear transformation of variables. We show that this method is difficult to apply and may produce an inaccurate measurement of the concept unless the exact functional form is chosen. Third, we suggest an alternative methodology, known as data envelopment analysis. This accounts for the challenges of the conventional methodology when we do not know the accurate functional form for nonlinear transformation, while performing as well as the best of the conventional approach. Finally, by using actual firm data, we show that our suggested methodology can be an effective alternative to the conventional approach of capturing a firm’s speed.
Keywords: AOM Annual Meeting Proceedings 2023; AOM Boston 2023; Research Methods; dept.mgt

When Does an Increase in a Firm’s Operational Effectiveness Reduce its Economic Performance? - Lee, Minjae (Academy of Management Proceedings, 2023)
Conventional wisdom suggests that an increase in a firm’s operational effectiveness will increase its economic performance. However, we show that an increase in a firm’s operational effectiveness can decrease its economic performance. Specifically, a firm’s increase in operational effectiveness of its existing projects following a positive demand shock can limit its profitable growth as its strategic resources are not allocated to pursuing new projects, thereby incurring opportunity costs that can lower its economic performance. We corroborate this reasoning in the context of the liquefied natural gas industry, which experienced a positive demand shock in 2000 due to energy market liberalization. We find empirically that a firm’s operational effectiveness increases its Tobin’s Q in the pre-shock period and reduces it in the post-shock period.
Keywords: AOM Annual Meeting Proceedings 2023; AOM Boston 2023; Strategic Management; dept.mgt

Understand the changes in motivation: comparative studies using theory-based interventions - Wang, Zheni; Briand, Melanie (Academy of Management Proceedings, 2023)
Managers often need to stay motivated and effectively motivate others. Therefore, they should rely on evidence-based interventions to manage the daily routine of motivational dynamics at work. This research answered how self-determination-theory-based interventions change employees’ motivation and motivational consequences during short time frames (i.e., within an hour, within a few weeks/months). Field study one focused on assessing the effectiveness of a one-day training workshop in helping improve managers’ work motivation, basic psychological needs satisfaction/frustration, and changing managers’ needs-supportive/thwarting behaviors within a few weeks. Results supported the training effectiveness as managers were rated less needs-thwarting by their direct subordinates and self-reported improvement in needs satisfaction/frustration six weeks after completing the training program. Online study two used the mean and covariance structure analysis and tested the three types of basic psychological needs supportive/thwarting and control conditions (3x2x1 factorial design) on the situational motivation, vitality, and general self-efficacy for playing online word games within 30 minutes. Multi-group confirmatory factor analysis (CFA) confirmed the scalar measurement invariance, then latent group means comparison results showed consistently lower controlled motivation across the needs-supportive and thwarting experimental conditions. During a quick online working scenario, the theory-based momentary intervention effectively changed situational extrinsic self-regulation in Amazon MTurk participants. Supplementary structural equation modeling (SEM) analyses using experience samples supported the indirect dual-path model from basic needs satisfaction to vitality and general efficacy via situational motivation. We discussed the theoretical implications of the temporal properties of work motivation, the practical implications on employee training and organizational change programs, and the limitations.
Keywords: AOM Annual Meeting Proceedings 2023; AOM Boston 2023; Organizational Behavior; dept.mgt

What explains the spread of corporate social responsibility? The role of competitive pressure and institutional isomorphism in the diffusion of voluntary adoption - Han, Seungmin; Ito, Kiyohiko (Journal of Management & Organization, 2023)
This study provides a new perspective on the determinants of the spread of voluntary corporate social responsibility (CSR) adoption by incorporating the potential role of its adoption by industry competitors. We find supportive evidence that firms make CSR adoption decisions in response to competitive pressure as well as institutional mimetic pressures. Based on an event history analysis of longitudinal data from a sample of 711 Korean publicly traded firms over a 12-year period, our findings suggest that the CSR behavior of competitors is positively associated with a focal firm's earlier adoption of CSR, leading to the diffusion of CSR across firms. Specifically, this study shows that the pure rivalry-driven pressure from non-leader competitors has a stronger positive relationship with earlier CSR adoption. The results also indicate that a firm's CSR adoption decision is accelerated by competitive rivalry as well as social pressures arising from institutional mimetic isomorphism.
Keywords: Competitive strategy; corporate social responsibility; dept.mgt; institutional theory; peer-reviewed; quantitative methods

The Evolving Landscape of International Consumer Data Privacy Compliance. - Pisano, Mark; Smith, Robert A.; Badr, Kauther S. (ACET Journal of Computer Education & Research, 2022)
Keywords: dept.bis; dept.mgt; peer-reviewed; ⛔ No DOI found

The Crisis of Danbury Fair Mall - Ahn, Jin Sun; Chung, Hanyong; Kim, Jung Hoon; Kim, Youngbin; Shin, Natalie Jungyoun (Journal of Marketing Development and Competitiveness, 2021)
This case describes the difficult financial situation of Danbury Fair Mall, which is the second biggest shopping mall in Connecticut. After World War II, the shopping mall business had grown fast especially in suburban areas of the U.S. However, the increasing popularity of online shopping caused extensive damage to shopping malls. This case will provide students the chance to think about the past, the present, and the future of the shopping mall industry in the U.S
Number: 2
Keywords: Connecticut; dept.acc; dept.mgt; peer-reviewed; ⛔ No DOI found

Arts-based pedagogy in management education: personal reflections - Yang, Charlie; Ivanova, Ekaterina; Ivanova, Maria (Honing Self-Awareness of Faculty and Future Business Leaders: Emotions Connected with Teaching and Learning, 2023)
Historically business education has put greater emphasis on rational analysis and the acquisition of instrumental and technical knowledge, while paying relatively scant attention to developing business students’ soft skills such as self- and social awareness and emotional intelligence through contemplative learning. In light of the growing need for more open and diverse ways of knowing that are more holistic, emotional, and aesthetic in management education, the authors present a 2 × 2 framework of arts-based pedagogy which helps organize various arts-based practices currently used in management education. The authors also share their personal reflections on using artful practices, specifically focussing on two individual-level experiential learning activities (i.e. museum visits and e-portfolio projects) and one group-based participatory art project. The authors further discuss why creative thinking and innovative arts-based practices can open up a new possibility for filling the gaps in current management education, especially in regard to developing students’ self- and social awareness and environmental consciousness in a more creative manner.
Keywords: Arts-based pedagogy; Digital photography; Electronic portfolio (e-portfolio); Museum learning; Participatory art; Socially engaged art; dept.mgt

Introduction to Business Law and Ethics - Badr, Kauther S.; Smith Jr, Robert A. (Kendall Hunt, 2022)
Keywords: dept.mgt

A Longitudinal Investigation of the Changes in Work Motivation and Employees’ Psychological Health - Wang, Zheni; Panaccio, Alexandra (Administrative Sciences, 2022)
Organizations strive to motivate employees to thrive at work. However, employees’ motivation is likely to vary over a short period (e.g., a few months) to cope with the routine dynamics of organizations’ activities. These motivation dynamics covary with employees’ affective, cognitive, and behavioral outcomes in the workplace. Moreover, employees’ psychological health, a multidimensional concept focused on the individual’s well/ill-being simultaneously, changes over time. Using the integrated theoretical frameworks of self-determination theory (SDT) and the hierarchical model of self-determined motivation (H-SDT), this research sought to examine the motivational changes following the dual-path model. In particular, this work sought to unpack the temporal dynamics in employees’ subjective well/ill-beings predicted by the changes in basic needs satisfaction/frustration through autonomous/controlled motivation, while considering the characteristics of people’s general causality orientations (trait-level motivation). Over four months, longitudinal field data were collected from the employees in several private small businesses in the consumer product retail industry. Latent growth modeling (LGM) results supported the positive dual relations between the changes in employees’ psychological health and basic psychological needs satisfaction/frustration, but neither the changes of autonomous/controlled work motivation nor the indirect change paths via autonomous/controlled work motivation were significant. Finally, we discussed the theoretical and practical implications of the findings. Limitations and possible future research directions to further this line of research on the dynamic of work motivation were also summarized.
0 citations (Crossref) [2023-10-31] Number: 4
Keywords: change in motivation; dept.mgt; longitudinal study; peer-reviewed; psychological health

Thriving in the dynamics: a multi-level investigation of needs-supportive features, situational motivation, and employees’ subjective well-being - Wang, Zheni; Panaccio, Alexandra (Current Psychology, 2023)
Employees often demonstrate various regulatory intentions toward multiple responsibilities they must fulfill on the job. Therefore, it is possible that employees’ motivation changes during the workday because of the various situations they have experienced and that these motivational fluctuations affect their subjective well-being across different activities. Following the integrated frameworks of the self-determination theory (SDT) and the hierarchical model of motivation (H-SDT), the present research studied the variations of employees’ daily motivation for work across different activities using the survey of day reconstruction method (DRM). Multi-level structural equation modeling (MSEM) was used to analyze the variations in the perceived three basic psychological (i.e., autonomy-, relatedness-, and competence-) needs-supportive features (NSFs), situational motivation, and variables capturing the employees’ subjective well-being (including vitality and positive/negative affect) laid out according to a list of work episodes in DRM. Results of this study confirmed that employees’ subjective well-being (mainly vitality and positive affect) were positively promoted by NSFs pertained to specific work activities via the indirect path of situational autonomous motivation at work. Furthermore, vitality and positive affect were also directly predicted by situational autonomous motivation. These empirical findings expanded the research evidence supporting employees’ subjective well-being as a multi-level and multi-dimensional dynamic motivational consequence promoted by configurable specific NSFs at work. We also discussed the limitations and future directions for this line of research.
Keywords: Dynamics of work motivation; Multi-level modeling; Psychological health; dept.mgt; peer-reviewed

Energy transitions and labor market patterns in the U.S. coal industry - Michieka, Nyakundi M.; Graziano, Marcello; Musso, Marta; Fouquet, Roger (Structural Change and Economic Dynamics, 2022)
The U.S. coal industry is in the midst of a transition. Changes in regulation and technological innovation from other fossils and renewables have affected its competitiveness. These could have significant impacts on the labor market where jobs could be lost. In this study, we investigate how changes in employment in the coal industry affect wages in 20 industries in 10 U.S. coal producing states. We assess how these transitions impact welfare programs, since coal producing regions are associated with higher poverty levels. Results show that in the long run, migration of coal workers decreased wages in the construction, manufacturing sectors. Point estimates reveal that an increase in separations of coal workers increase Supplemental Nutrition Assistance Program (SNAP) caseloads. In states where coal mining has a smaller contribution to GDP, an increase in coal employment increases SNAP caseloads.
7 citations (Crossref) [2023-10-31]
Keywords: Labor market dynamics; dept.mgt; peer-reviewed

The spatial dimension of energy transition policies, practices and technologies - Caragliu, A.; Graziano, M. (Energy Policy, 2022)
2 citations (Crossref) [2023-10-31]
Keywords: dept.mgt; peer-reviewed

Servant leadership and employee wellbeing: A crosscultural investigation of the moderated path model in Canada, Pakistan, China, the US, and Brazil - Wang, Zheni; Panaccio, Alexandra; Raja, Usman; Donia, Magda; Landry, Guylaine; Pereira, Michelle Morelo; Ferreira, Maria Cristina (International Journal of Cross Cultural Management, 2022)
Drawing on samples from Canada, Pakistan, China, the US, and Brazil comprising over 800 employees, we examined whether servant leaders (SL) - characterized as putting the needs of others above their own - promote employees’ well-being via autonomous motivation, accounting for employees’ power distance and collectivism values as moderating variables. Autonomous motivation, a type of self-regulation, sustains one’s well-being. Personal values facilitate one’s work behaviors cross-culturally. Multigroup confirmatory factor analysis (CFA) results confirmed matrix invariance of all the measures. The path and moderation analyses result using multilevel structural equation modeling (SEM) supported the positive direct and indirect paths among SL, autonomous motivation, and psychological well-being across the five cultures; Collectivistic value negatively moderated the relationship between servant leadership and autonomous motivation across the Chinese and US samples. In addition, with only a limited number of items, measurements of SL and vitality achieved scalar invariance. ANOVA test results also confirmed the significant comparative differences in these two variables among the cultural groups. Findings in this research provided robust and empirical support for the motivational effects of the servant leadership theory across the globe. Theoretical and practical implications for evidence-based cross-cultural management practices and future directions for leadership training in diverse cultural contexts are discussed.
0 citations (Crossref) [2023-10-31]
Keywords: Servant leadership; autonomous motivation; dept.mgt; peer-reviewed; personal values; psychological well-being

A Data-Driven Algorithm to Redefine the U.S. Rural Landscape: Affinity Propagation as a Mixed-Data/Mixed-Method Tool - Heumann, Benjamin W.; Graziano, Marcello; Fiaschetti, Maurizio (Economic Development Quarterly, 2022)
This study demonstrates the application of affinity propagation as a data-driven approach to identifying and mapping typologies of place along the urban-rural continuum. The authors characterize Zip Code Tabulation Areas using demographic, economic, land cover, and accessibility to transportation infrastructure, which results in 22 clusters, 15 of which have a major rural component. The spatial pattern of these clusters varies, reflecting the heterogeneity in U.S. rurality. Rural is not a single concept that can be simply defined by population density. By comparing three economic indicators before and after the global financial crisis of 2007 to 2012, the authors find that the degree of economic recovery is captured by rural typologies. They compare both the methodological results and analysis of socioeconomic resilience to two of the most used threshold-based regional typologies, one developed by the U.S. Department of Agriculture Economic Research Service and one used by the American Communities Project.
0 citations (Crossref) [2023-10-31]
Keywords: dept.mgt; peer-reviewed; rural data; rural demography; rural development

The many sizes and characters of the Blue Economy - Graziano, M.; Alexander, K.A.; McGrane, S.J.; Allan, G.J.; Lema, E. (Ecological Economics, 2022)
This article analyses the economic size and resilience of five established definitions of the Blue Economy across two geographical locations: Scotland (UK) and Michigan (USA). The article analyses sector-level employment, labor productivity and Gross Value Added (GVA) data, and uses graphical representations to highlight the differences in conceptualizing the Blue Economy in ways that affect its weight and contribution to regional economies. Further, it analyses how each definition has fared in the post-2007/2011 crisis, assessing their resilience. This novel work tackles the emerging discourse around the Blue Economy by highlighting its regional character, and by problematizing the divergent definitions of the concept. © 2022 Elsevier B.V.
6 citations (Crossref) [2023-10-31]
Keywords: Blue Economy; Employment; Regional analysis; Wages; dept.mgt; peer-reviewed

The Effect of Higher Education on Youth Unemployment in European Regions During a Period of Economic Instability - Hermannsson, K.; Scandurra, R.; Graziano, M. (Journal of Education Finance, 2020)
This paper examines the impact of higher education on youth unemployment. Following the 2008 financial crisis, youth unemployment returned to the fore as a serious concern among policy makers in Europe. A crucial difference from previous recessions is that this time around supply of higher education opportunities was much higher than in the 1980s, and indeed higher education participation rates grew rapidly in many regions during this period. Drawing on previous work on youth unemployment and the economic impacts of education we identify a variety of channels through which higher education is likely to influence youth unemployment. We examine this issue using a macro-panel of European regions for the period 2002-2012. This decade was characterized by variation in economic activity and higher education rates. Our results suggest that expansion of higher education during this period had a mitigating effect on youth unemployment and not recognizing this external benefit of education risks underestimating the effects of macroeconomic shocks on young people. © 2020, University of Illinois Press. All rights reserved.
Keywords: dept.mgt; peer-reviewed; ⛔ No DOI found

Effect of a brief social contact video on transphobia and depression-related stigma among adolescents: A randomized clinical trial - Amsalem, D.; Halloran, J.; Penque, B.; Celentano, J.; Martin, A. (JAMA Network Open, 2022)
Importance: Transphobia and stigma remain barriers to seeking mental health care for gender-diverse adolescents. Objective: To examine the utility of brief social contact-based video interventions of transgender protagonists with depression to reduce transphobia and depression-related stigma and increase treatment-seeking intentions among adolescents in the general population. Design, Setting, and Participants: During August 2021, a total of 1437 participants were recruited and randomly assigned to 1 of 4 video-based conditions in a 2:2:1:1 ratio: (1) transgender adolescent girls, (2) transgender adolescent boys, (3) cisgender adolescent girls, or (4) cisgender adolescent boys. Interventions: In each of the approximately 110-second videos, an empowered presenter shared their personal story about coping with depression and reaching out for help. Main Outcomes and Measures: The primary outcome was the score on the Attitudes Toward Transgender Men and Women (ATTMW) scale. Secondary outcomes were (1) a "gender thermometer" rating for warmth in transgender perception, (2) the Depression Stigma Scale (DSS) score, and (3) the General Health-Seeking Questionnaire (GHSQ) score. Results: Of the 1437 randomized participants, 1098 (76%) completed the postintervention assessment and passed all the validity tests (mean [SD] age, 16.9 [1.2] years; 481 [44%] male; 640 [58%] White). A significant change in attitudes toward transgender youth was found within the intervention group only (mean [SD] ATTMW scores: intervention group, 34.6 [23.1] at baseline to 32.8 [24.2] after intervention; P ¡.001; control group, 33.5 [23.4] at baseline to 32.4 [24.1] after intervention; P =.01). The mean (SD) total DSS scores decreased significantly across study groups (intervention: 1.3 [3.3]; control: 1.7 [3.3]; P ¡.001). A significant increase in intention to seek help from a parent was found in the intervention (mean [SD] GHSQ score, 0.2 [1.1]) and control (mean [SD] GHSQ score, 0.3 [1.2]) groups (P ¡.001), as was a decrease in those not wanting to seek help from anyone (mean [SD] GHSQ score: intervention, 0.2 [1.6], P =.009; control, 0.3 [1.2], P ¡.001) Secondary analyses revealed significant differences in baseline ATTMW scores and intervention effects between transgender and gender-diverse and cisgender participants and between lesbian, gay, bisexual, or queer (LGBQ) and straight participants (F = 36.7, P ¡.001) and heterosexual participants (F = 37.0, P ¡.001). A significant difference was also found in mean (SD) transgender warmth scores from baseline to after intervention between groups (2.6° [13.1°] in the intervention group vs 0.4° [8.3°] in the control group; P ¡.001). Conclusions and Relevance: In this randomized clinical trial, brief social contact-based videos proved efficacious in reducing transphobia and depression-related stigma and in increasing treatment-seeking intentions among adolescents in the general population. By personifying, individualizing, and providing face and voice to the experience of transgender youth, other adolescents, especially those who are cisgender and/or of a heterosexual orientation, can gain empathetic insights into the lives of their often marginalized and stigmatized fellow youth. Trial Registration: ClinicalTrials.gov Identifier: NCT04969003. © 2022 Collabra: Psychology. All rights reserved.
10 citations (Crossref) [2023-10-31] tex.art_number: e220376 tex.document_type: Article tex.pubmed_id: 35212749 tex.source: Scopus
Keywords: Adolescent; Depression; Female; Humans; Male; Patient Acceptance of Health Care; Prejudice; Social Stigma; Transgender Persons; Video Recording; adolescent; controlled study; depression; dept.mft; dept.swk; female; human; male; patient attitude; peer-reviewed; prejudice; psychology; randomized controlled trial; social stigma; transgender; videorecording

The US Blue New Deal: What does it mean for just transitions, sustainability, and resilience of the blue economy? - Axon, S.; Bertana, A.; Graziano, M.; Cross, E.; Smith, A.; Axon, K.; Wakefield, A. (Geographical Journal, 2022)
The ocean and coasts are largely absent from the “Green New Deal” proposal. In response to the limited attention paid to the sustainability and equitable governance approaches of the blue economy, a US “Blue New Deal” has been proposed aiming to protect the health of the ocean and support coastal communities' adaptation to climate change. The Blue New Deal emerged as a central policy proposal from 2020 Democratic presidential candidate Elizabeth Warren to enhance the role of the blue economy while simultaneously addressing the climate crisis. Through a just transitions analysis, this article evaluates the proposal for a US Blue New Deal — as designed by Senator Elizabeth Warren — that would be applied towards enhancing socioeconomic resiliency, environmental justice, and addressing social inequities. As part of a critical policy analysis evaluating the areas of focus Warren's Blue New Deal presents, environmental justice and sustainability are central to the success of managing, and enhancing the role of, the blue economy. The challenges facing the Blue New Deal reflect a “one size fits all” federal approach that has implications for addressing multifaceted obstacles in key sectors of the blue economy, its governance, and tackling interconnected crises that exacerbate socioeconomic inequities and vulnerabilities of marginalised coastal communities. This article proposes a blue justice framework for the Blue New Deal that seeks to address the tensions and contradictions that exist in its current form and indicates how a comprehensive policy framework can enhance the sustainability and equitable involvement of the blue economy. The information, practices and views in this article are those of the author(s) and do not necessarily reflect the opinion of the Royal Geographical Society (with IBG). © 2022 Royal Geographical Society (with the Institute of British Geographers).
3 citations (Crossref) [2023-10-31] tex.coden: GGJOA tex.document_type: Article tex.source: Scopus
Keywords: dept.egm; dept.mgt; dept.soc; peer-reviewed

Manipulating common method variance via experimental conditions - Wall, A.E.; Simmering, M.J.; Fuller, C.M.; Waterwall, B. (Electronic Journal of Business Research Methods, 2022)
Research data collected from single respondents may raise concerns regarding common method variance (CMV), which is believed to threaten the validity of findings. The primary concern is that CMV can inflate substantive relationships, such that they appear statistically significant when they are not. Thus, understanding the nature of CMV is critical, especially when one considers the popularity—and sometimes necessity—of using self-report data. Research examining CMV has found conflicting evidence about the impact of CMV. Researchers who believe CMV influences findings have proposed solutions to combat any real or perceived potential bias, including changing survey instructions and using marker variables, but few studies have examined the efficacy of these approaches. The purpose of this study is to examine the impact of these techniques and the nature of CMV using an experimental design. To conduct the experiment, multiple versions of a survey, which vary in their use of the remedial approaches, are utilized to collect data, which resulted in 1,069 usable responses. The experimental design was based on the faking literature and included instructions intended to induce or reduce the levels of CMV. Further, two different marker variables are used to determine the degree to which they create a psychological separation in substantive variables. Correlation analysis and measurement invariance are used to analyze the data. This study posits that, if CMV is a substantial concern for self-report data and these approaches are effective, then findings will differ in surveys that incorporate such approaches from surveys that do not. Results indicate few differences in experimental conditions, meaning that regardless of instructions or marker variable, substantive item correlations remained statistically similar. The results indicate this is likely due to the minimal impact of CMV, given that the proposed methods of correction did not significantly influence research findings. These findings have implications for researchers in that they do not support that CMV, or at least its proposed remedies, significantly alter findings. However, support for the null conclusions, in spite of appropriate statistical power, warrant future research examining the nature and impact of CMV. © 2022,lectronic Journal of Business Research Methods. All Rights Reserved.
1 citations (Crossref) [2023-10-31] tex.author_keywords: Common method variance; Experiment; Marker variable; Psychological separation; Same source research tex.document_type: Article tex.source: Scopus
Keywords: dept.mgt; peer-reviewed

The Detrimental Effects of Ethical Incongruence in Teams: An Interactionist Perspective of Ethical Fit on Relationship Conflict and Information Sharing - Shin, Natalie J.; Ziegert, Jonathan C.; Muethel, Miriam (Journal of Business Ethics, 2021)
Building from an interactionist view of ethics, this study sought to integrate individual and contextual factors for understanding ethical perceptions in teams. Given the proximal nature of team members, this study specifically explored how individuals comparatively evaluate their own ethical behaviors and team members’ ethical behaviors to arrive at a perception of ethical person–group (P–G) fit within a team. Grounding our theoretical arguments in relational schemas theory (Baldwin, Psychological Bulletin 112:461–484, 1992), we demonstrate that interpersonal ethical perceptions can have distal impacts on perceptions of team functioning. The results support the hypotheses that a perceived ethical incongruence between the self and other team members (i.e., lack of ethical P–G fit) negatively influenced perceptions of relationship conflict and ultimately information sharing. By exploring individual and team level aspects of ethics concurrently, we contribute to a deeper understanding of contextual forces in ethics through an interactionist approach.
1 citations (Crossref) [2023-10-31]
Keywords: dept.mgt; peer-reviewed

Using contemplative photography in transformative sustainability management education: Pedagogical applications in the united states, russia and germany - Yang, Charlie; Ivanova, Ekaterina; Hufnagel, Julia (The International Journal of Management Education, 2021)
Developing a sustainability mindset requires a transdisciplinary approach to business education that integrates a rational-analytic mode of thinking and an emotive-holistic understanding of the human mind. In order to cultivate the sustainability mindset of business students, we have designed a contemplative art-based project involving the creation of an electronic portfolio which consists of a student's digital photographs. We have integrated it into our teaching of management courses in the United States, Russia, and Germany, respectively. The project aims to enable business students to become more visually attentive and environmentally conscious, so that they will pay close attention to the process of building more sustainable relationships within their natural and social environments. From the interpretative phenomenological perspective, we have analyzed the students' e-portfolios in order to understand how business students make sense of environmental and human sustainability. While envisioning more transformative sustainability management education, we have also discussed the pedagogical implications of making the e-portfolios for enhancing the students' understanding of the sustainability mindset. © 2021 Elsevier Ltd
3 citations (Crossref) [2023-10-31] https://publications.hse.ru/articles/523564895
Keywords: dept.mgt; peer-reviewed

Socio-economic impacts of the Great Lakes restoration initiative - Liesch, Matthew; Graziano, Marcello (Geographical Review, 2021)
Interviews illuminate impacts of the Great Lakes Restoration Initiative (GLRI), a United States’ federal program designed to improve the Great Lakes by restoring the region’s most polluted harbors and coastal landscapes. To see how GLRI funds caused changes in the built environment and to attitudes toward place, semi-structured interviews were conducted with private- and public-sector leaders. Case studies are four EPA-designated Areas of Concern receiving substantial GLRI funds in Buffalo, New York; Duluth-Superior, Minnesota and Wisconsin; Muskegon, Michigan, and Sheboygan, Wisconsin. Results show that GLRI serves as a catalyst in three principal ways: The program leveraged local and state funds, both private and public. GLRI also leads to greater socio-spatial consciousness regarding rehabilitated places. Also, GLRI had led to stronger and deeper senses of place. This study reveals interviews help to calculate a more holistic return on investment for a prominent federal program. This study offers a way forward for ecosystem services research to take a more holistic view than has traditionally been done, in that semi-structured interviews illuminate impacts that traditional economic modeling alone cannot. Concurrently, this research is an example of how a prominent federal program affects community perceptions integral to holistic coastal planning processes. © Copyright © 2021 by the American Geographical Society of New York.
3 citations (Crossref) [2023-10-31]
Keywords: dept.mgt; peer-reviewed

Validity and reliability of the lode excalibur sport cycle ergometer for the wingate anaerobic test. - Lunn, William R.; Axtell, Robert S. (Journal of strength and conditioning research, 2021)
https://europepmc.org/article/MED/31453946 ; https://pubmed.ncbi.nlm.nih.gov/31453946/ ; https://dialnet.unirioja.es/servlet/articulo?codigo=8169588
Keywords: dept.mgt; peer-reviewed; ⛔ No DOI found

Environmental performance, environmental management and company valuation - Abrams, Roy; Han, Seungmin; Tanzeeb Hossain, Mehdi (Journal of Global Responsibility, 2021)
Purpose: This paper aims to investigate the relationship between environmental performance and management and company valuation. With a specific focus on company valuation, this study shows how a firm’s environmental activities, including its environmental management practices, are perceived and valued by its stockholders. Design/methodology/approach: Newsweek’s green ranking data between 2014 and 2016 were used to support this analysis. Environmental performances and environmental management practices of 345 Fortune 500 companies from various industries were included in the data set. Findings: The analysis finds higher valuations for US companies that are more efficient in managing greenhouse gas emissions. In addition, it empirically shows that investors place a higher value on companies with the following environment-related management policies: initiatives that reward top management for achieving environmental goals and third-party auditing of environmental performance. Originality/value: By incorporating corporate environmental management practices as an additional environmental performance criterion, this research fills a gap in the literature on the potential relationship between corporate environmental performance and company valuation. © 2021, Emerald Publishing Limited.
6 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85118117232
Keywords: dept.mgt; peer-reviewed

Legacy and shockwaves: A spatial analysis of strengthening resilience of the power grid in Connecticut - Gallaher, Adam; Graziano, Marcello; Fiaschetti, Maurizio (Energy Policy, 2021)
Grid resilience and reliability are pivotal in the transition to low and zero carbon energy systems. Tree-trimming operations (TTOs) have become a pivotal tool for increasing the resilience power grids, especially in highly forested regions. Building on recent literature, we aim at assessing the temporal and spatial extents of the benefits that TTOs produce on the grid from three perspectives: the frequency, extent, and duration of outages. We use a unique dataset provided by Eversource Energy, New England's largest utility company, with outage events from 2009 to 2015. We employ spatial econometrics to investigate both the legacy and spatial extent of TTOs. Our results show TTOs benefits occur for all three metrics for at least 4 years, and benefits spillover to up to 2 km throughout the treated areas, with significant spatial spillovers across the state greater than direct effects. Implications lead to supporting TTOs as part of the hardening policies for utility companies, especially as home-based activities increase in importance in a post-COVID19 world. © 2021 Elsevier Ltd
12 citations (Crossref) [2023-10-31] https://discovery.ucl.ac.uk/id/eprint/10138230/ ; https://www.sciencedirect.com/science/article/pii/S0301421521004523
Keywords: COVID-19; Connecticut; Economics; Electric power transmission networks; Energy transitions; Low carbon; Outages; Power grids; Spatial analysis; Spatial extent; Spatial modelling; Statistics; Tree trimmings; Trimming; Trimming operations; United States; Utilities companies; Vegetation management; atmospheric electricity; data set; dept.mgt; econometrics; electricity; smart grid; spatiotemporal analysis; utility sector

Integrating returns and costs in examining faster firm speed - Lee, Minjae (Academy of Management Proceedings, 2021)
0 citations (Crossref) [2023-10-31]
Keywords: dept.mgt

A data-based approach to identifying regional typologies and exemplars across the urban–rural gradient in Europe using affinity propagation - Fiaschetti, Maurizio; Graziano, Marcello; Heumann, Benjamin W. (Regional Studies, 2021)
We apply recent developments in data-mining and statistics, using affinity propagation (AP) to identify regional typologies in the European Union (EU) and characterize major factors between rural–rural and rural–urban regional differences, without predetermined thresholds. We identify a representative ‘exemplar’ within each cluster using the drivers of Copus enriched with climate and land-cover/land-use variables to provide geographical context and pinpoint differences driven by natural and human–natural landscapes. Building upon the works of Dijkstra and the Eudora Project, we expand the dimensions of regional differences, introducing a threshold-less, data-driven model able to identify exemplars, and the main characteristics of each cluster or regional typology. © 2021 Regional Studies Association.
5 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85100769962
Keywords: Europe; European Union; data mining; dept.mgt; economic development; peer-reviewed; regional development; urban-rural migration

A comparison of two multilingual meeting systems - Aiken, Milam; Park, Mina (International Journal of Computers & Technology, 2020)
0 citations (Crossref) [2023-10-31]
Keywords: Google Translate; dept.bis; dept.mgt; peer-reviewed

Increasing demand and a tradeoff between speed-cost efficiencies and total profits - Lee, Minjae (Academy of Management Proceedings, 2020)
0 citations (Crossref) [2023-10-31]
Keywords: dept.mgt

Developing the elusive construct of speed-cost efficiency - Lee, Minjae; Mahoney, Joseph T. (Academy of Management Proceedings, 2020)
0 citations (Crossref) [2023-10-31]
Keywords: dept.mgt

A temporal analysis of employees’ situational work motivation and well- being - Wang, Zheni; Panaccio, Alexandra Joelle (Academy of Management Proceedings, 2020)
0 citations (Crossref) [2023-10-31]
Keywords: dept.mgt

Thinkubator Approach to Solving the Soft Skills Gap - Stewart, Carol; Marciniec, Sheryl; Lawrence, Denval; Joyner-McGraw, Laquita (American Journal of Management, 2020)
0 citations (Crossref) [2023-10-31]
Keywords: dept.mgt; peer-reviewed

A Self-Determination Approach to Understanding Individual Values as an Interaction Condition on Employees' Innovative Work Behavior in the High-Tech Industry - Wang, Zheni; Gao, Mengchan; Panaccio, Alexandra (Journal of Creative Behavior, 2021)
Drawing on self-determination theory (SDT; E.L. Deci & R.M. Ryan, 1985, 2000) and using corporate samples (N = 284; 63% Male; Mean Age = 34, SD = 6.09) from high-tech firms in China, this empirical study explored the path model from satisfaction of the basic psychological needs for autonomy, competence, and relatedness, through autonomous motivation to employees' innovative work behavior (“IWB”; J. De Jong & D. Den Hartog, 2010). It also simultaneously examined the interactions between autonomous work motivation and individual values (collectivism, H.C. Triandis (1995); uncertainty avoidance, R. J. House, P. J. Hanges, M. Javidan, P. W. Dorfman, & V. Gupta (2004); and power distance, J. Farh, R.D. Hackett, & J. Liang (2007)) in the conditioned path model. The regression results obtained from conditional PROCESS analysis (A.F. Hayes, 2013, 2018) suggest that basic psychological needs satisfaction is positively related to employees' IWB via autonomous motivation, but that these indirect effects were weaker when employees' power distance value orientation was high. Implications, limitations, and future research directions are discussed. © 2020 by the Creative Education Foundation, Inc.
14 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85082766274
Keywords: dept.mgt; peer-reviewed

Uncovering Relations Between Leadership Perceptions and Motivation Under Different Organizational Contexts: a Multilevel Cross-lagged Analysis - Gagné, Marylène; Morin, Alexandre J. S.; Schabram, Kira; Wang, Zhe Ni; Chemolli, Emanuela; Briand, Mélanie (Journal of Business and Psychology, 2020)
Surprisingly scant research has adequately examined directional influences between different perceptions of managerial leadership behaviors and different types of work motivation, and even fewer studies have examined contextual moderators of these influences. The present study investigated longitudinal and multilevel autoregressive cross-lagged relations between perceptions of transformational, transactional, and passive-avoidant leadership with autonomous motivation, controlled motivation, and amotivation. Multilevel longitudinal models were estimated on data from 788 employees, nested under 108 distinct supervisors, from six Canadian organizations. Results revealed that perceptions of leadership behaviors predicted changes in motivation mostly at the collective level and that some of these relations changed as a function of whether organizations had recently faced a crisis. Collective perceptions of transformational leadership were related to increased collective autonomous and controlled motivation, while individual controlled motivation was related to increased individual perceptions of transactional leadership. In organizations facing a crisis, individual perceptions of transactional leadership were related to decreased individual controlled motivation, while collective perceptions of transactional leadership were related to increased collective autonomous motivation and decreased collective amotivation. In organizations not facing a crisis, collective perceptions of transactional leadership were related to decreased collective autonomous motivation. Implications for theory and practice are discussed.
11 citations (Crossref) [2023-10-31] tex.ids: gagneUncoveringRelationsLeadership2020, lens.org/066-744-892-590-102, pop00060 tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85071718155 tex.type: [object Object] type: Article
Keywords: Autonomous motivation; Multilevel modeling; Transactional leadership; Transformational leadership; dept.mgt; peer-reviewed

Family Law and Practice - Luppino, Grace A.; Miller, Justine FitzGerald (Pearson, 2020)
For courses in family law for students in paralegal studies programs, broader legal studies programs, and those majoring in criminal justice, social work, and education. Connecting theory, history, and practice in family law Family Law and Practice prepares students to enter the workplace with a firm grasp of family law and procedural components of family law practice. To meet this challenge, the authors have divided the 5th edition into two parts: the first introducing the principles of family law and the second translating theory into practice. The new edition also addresses changing views on marriage, spousal roles, children’s status in the family, and even what constitutes a family. It also adds cases, statutes, and legal forms from a variety of US states to engage students across the country.
Keywords: Domestic relations; Handbooks; manuals; etc; United States; United States; Legal assistants; dept.mgt; faculty_collection